Analysis of factors affecting interests of student for saving on sharia financial institution; case study of Raudlatut Thalibin Leteh Rembang boarding school - Susi Rahayu; Rosida Dwi Ayuningtyas; Maskudi Maskudi (Faculty of Business & Economics, Universitas Islam Indonesia, 2020)
Purpose: This study aims to examine the influences of religiosity, knowledge, and income toward the interest to open savings account in a sharia bank on students of Raudltut Thalibin Leteh boarding school in Rembang.Methodology: This study uses a survey with a sample of 100 students of Raudltut Thalibin Leteh boarding school in Rembang. Data analysis used in this study is SEM with AMOS software assistance. This research uses quantitative method. Data analysis used in this study is multiple linear regression analysis, classical assumption test, and t-test (Hypothesis Test).Findings: From the result of this research, it can be concluded that Knowledge (X2) and Income (X3) have an effect on interest to open saving account in sharia bank (Y). Meanwhile, trust (X1) has no effect on the interest to open saving account in sharia bank (Y).Originality: This study enriches the discussion in the literature by testing the influence of religiosity, knowledge and income in the context of Islamic boarding school students.